Prevalence and factors related to COVID‐19 vaccine hesitancy and unwillingness in Canada: A systematic review and meta‐analysis. Issue 1 (3rd October 2022) - Cénat, Jude Mary; Noorishad, Pari‐Gole; Moshirian Farahi, Seyed Mohammad Mahdi; Darius, Wina Paul; Mesbahi El Aouame, Aya; Onesi, Olivia; Broussard, Cathy; Furyk, Sarah E.; Yaya, Sanni; Caulley, Lisa; Chomienne, Marie‐Hélène; Etowa, Josephine; et al.
Abstract: This systematic review and meta‐analysis examined the prevalence and factors associated with vaccine hesitancy and vaccine unwillingness in Canada. Eleven databases were searched in March 2022. The pooled prevalence of coronavirus disease 2019 (COVID‐19) vaccine hesitancy and unwillingness was estimated. Subgroup analyses and meta‐regressions were performed. Out of 667 studies screened, 86 full‐text articles were reviewed, and 30 were included in the systematic review. Twenty‐four articles were included in the meta‐analysis; 12 for the pooled prevalence of vaccine hesitancy (42.3% [95% CI, 33.7%–51.0%]) and 12 for vaccine unwillingness (20.1% [95% CI, 15.2%−24.9%]). Vaccine hesitancy was higher in females (18.3% [95% CI, 12.4%−24.2%]) than males (13.9% [95% CI, 9.0%−18.8%]), and in rural (16.3% [95% CI, 12.9%−19.7%]) versus urban areas (14.1% [95%CI, 9.9%−18.3%]). Vaccine unwillingness was higher in females (19.9% [95% CI, 11.0%−24.8%]) compared with males (13.6% [95% CI, 8.0%−19.2%]), non‐White individuals (21.7% [95% CI, 16.2%−27.3%]) than White individuals (14.8% [95% CI, 11.0%−18.5%]), and secondary or less (24.2% [95% CI, 18.8%−29.6%]) versus postsecondary education (15.9% [95% CI, 11.6%−20.2%]). Factors related to racial disparities, gender, education level, and age are discussed.